Image of war and hybrid warfare - Johannes Schmidt, Johannes Schmidt (2023)
War images Hybrid warfare in and around Ukraine has confronted Europe with a security policy paradigm shift since 2014. The surprise takeover of Crimea by masked Russian soldiers without insignia in February/March 2014 and the Kremlin's initial denial of connection to it have shaped the image of a hybrid form of warfare worldwide. The subsequent military conflict in the east of Ukraine with separatism supported by neighboring states and the armed establishment and military security of newly created so-called people's republics (Donetsk, Luhansk), with recourse, among other things, to "Russian fighters on vacation" further reinforced this perception. For eight years, the pursuit of plausible deniability of Moscow's official involvement was the focus of Russia's actions in the hybrid trench warfare in Donbas. With Russia's large-scale military attack on Ukraine on February 24, 2022, what Russia called a "special military operation", the Ukrainian war has entered a new, militarily escalating but no less hybrid phase. This attack triggered strong reactions from the West and led to the declaration of a...